Formulation and Characterization of Ondansetron Hydrochloride Matrix Tablets for Sustained Drug Delivery (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The objective of proposed work was to develop Ondansetron Hydrochloride (OND HCl) sustained release matrix tablets for the better treatment of vomiting for extended period of time. Sustained release matrix tablet is the drug delivery system that is designed to achieve a prolonged therapeutic effect by continuously releasing medication over an extended period of time after administration of single dose. The matrix tablets of OND HCl were prepared by direct compression method using varying ratio of hydroxy propyl methyl cellulose (HPMC) and ethyl cellulose. The bends of tablets were evaluated for bulk and tapped density, % compressibility index and angle of repose and powder of all formulations blend exhibited that low interparticle friction and excellent flow characteristics. The prepared matrix tablets were then assessed for different physical tests like consistency of weight, thickness, hardness, friability, drug content and in vitro drug release. Each batch of the OND HCl matrix tablets were of good quality as to hardness, thickness, friability and % medicament content. The in vitro drug release study was done for 2 hours by utilizing paddle technique in 0.1N HCl (pH 1.2) as dissolution media and 6 hours using phosphate buffer (pH 6.8) as dissolution media. The drug release study showed that all formulation FMT-1, FMT-2, FMT-3, FMT-4, FMT-5 and FMT-6 were provide the drug release on sustained manner up to 8 hrs. Amongst the developed matrix tablets formulations, FMT-2 containing ethyl cellulose (100 mg) was optimized as best because FMT-2 show highest drug release profile and promoting the sustained release of drug, which could potentially improve the patient compliance.